Notes on the natural history of the Johore banana Musa gracilis holttum - Kiew, Ruth (Malaysian Nature Society, 1987)
Musa gracilis is the only wild banana species in Johore, Malaysia. In Kelantan and Trengganu it grows together with M. acuminata Colla. M. gracilis and M. violascens Ridley (in section Callimusa) are compared. Both are endemic to Peninsular Malaysia but their geographic distribution does not overlap. The anatomy of the seed of M. gracilis is described and the function of the chalazal mass is discussed. Growth (increase in stem height and rate of leaf production), its ecology and conservation status are also mentioned